A Lewis Acid Stabilized Ketenimine in an Unusual Variant of the Electrophilic Aromatic Substitution. Issue 67 (7th October 2022) - Surkau, Jonas; Bläsing, Kevin; Bresien, Jonas; Michalik, Dirk; Villinger, Alexander; Schulz, Axel
Abstract: Electrophilic aromatic substitution (EAS) can provide a straightforward approach to the efficient synthesis of functionalized complex aromatic molecules. In general, Lewis acids serve as a beneficial stimulus for the formation of a Wheland complex, the intermediate in the classical SE Ar mechanism of EAS, which is responsible for H/E (E=electrophile) substitution under formal H + elimination. Herein, we report an unusual variant of EAS, in which a complex molecule such as the tricyanomethane, HC(CN)3, is activated with a strong Lewis acid (B(C6 F5 )3 ) to the point where it can finally be used in an EAS. However, the Lewis acid here causes the isomerization of the tricyanomethane to the ketenimine, HN=C=C(CN)2, which in turn directly attacks the aromatic species in the EAS, with simultaneous proton migration of the aromatic proton to the imino group, so that no elimination occurs that is otherwise observed in the SE Ar mechanism. By this method, it is possible to build up amino‐malononitrile‐substituted aromatic compounds in one step. Abstract : By the action of a strong Lewis acid, isomerization of the tricyanomethane to the ketenimine, HN=C=C(CN)2, is triggered, which in turn directly attacks an aromatic species in an electrophilic aromatic substitution.